Genome size variation and polyploidy prevalence in the genus Eragrostis are associated with the global dispersal in arid area - Hutang, Ge-Ran; Tong, Yan; Zhu, Xun-Ge; Gao, Li-Zhi (Frontiers in Plant Science, 2023)
Biologists have long debated the drivers of the genome size evolution and variation ever since Darwin. Assumptions for the adaptive or maladaptive consequences of the associations between genome sizes and environmental factors have been proposed, but the significance of these hypotheses remains controversial. Eragrostis is a large genus in the grass family and is often used as crop or forage during the dry seasons. The wide range and complex ploidy levels make Eragrostis an excellent model for investigating how the genome size variation and evolution is associated with environmental factors and how these changes can ben interpreted. In this study, we reconstructed the Eragrostis phylogeny and estimated genome sizes through flow cytometric analyses. Our phylogenetic analyses support the monophyly of Eragrostis. Our results further showed that the genome sizes in Eragrostis ranged from ~0.66 pg to ~3.80 pg. Phylogenetic comparative analyses were performed to explore how genome size variation and evolution is related to their climatic niches and geographical ranges. The genome size evolution and environmental factors were examined using different models to study the phylogenetic signal, mode and tempo throughout evolutionary history. We found that a moderate phylogenetic conservatism existed in terms of the genome sizes but was absent from environmental factors. In addition, phylogeny-based associations revealed close correlations between genome sizes and precipitation-related variables, indicating that the genome size variation mainly caused by polyploidization may have evolved as an adaptation to various environments in the genus Eragrostis. This is the first study to take a global perspective on the genome size variation and evolution in the genus Eragrostis. Our results suggest that the adaptation and conservatism are manifested in the genome size variation, allowing the arid species of Eragrostis to spread the xeric area throughout the world.